From Leaf to Lip: Tracing Contaminants in Aceh's Traditional Chewing Tobacco (Bakông Asóê) - Rizka Auliatul Jannah; Qurrata Akyuni; Faradilla Faradilla; Elisa Purwaendah; Muhammad Diah; Rinaldi Idroes; Khairan Khairan (Graha Primera Saintifika, 2023)
Bakông Asóe is a typical Acehnese snack loved by older people in Aceh since ancient times. This snack is made from wet tobacco which is used as chewing tobacco. The process of drying Bakông Asóê in the open triggers heavy metal contamination by air pollution from motor vehicles. The process of storing Bakông Asóê in a wet state also triggers the growth of microbes such as bacteria and fungi due to a growth medium in the form of water. The purpose of this study was to determine the content of heavy metal contamination (Pb, Cd, Se, Cu and Hg) and microbiological contamination in the form of bacteria (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa) and fungi (Candida albicans and Aspergillus niger) in Bakông Asóê which sold on the side of the road without adequate hygiene. The research refers to a qualitative research approach with the type of research that is descriptive research. This study showed that heavy metal exposure in the form of Pb, Cu and Se in the three samples was still in the safe range for consumption. However, exposure to heavy metals in the form of Cd and Hg in the three samples exceeded the consumption standard. The results of the analysis of microbiological contamination in the three Bakông Asóê samples were proven to contain bacterial and fungal contamination, where cocci-shaped bacteria were more commonly found and fungi with the genus Aspergillus sp were also more dominant in the three Bakông Asóê samples. The conclusion of this study is positive for chemical and microbiological contamination in Bakông Asóê, which is sold in Aceh, Ule Kareng and Lambaro Markets.